PELATIHAN MENULIS KARYA TULIS ILMIAH MAHASISWA PRODI PARIWISATA UNIVERSITAS MUHAMMADIYAH TANGERANG TAHUN AJARAN 2023-2024 - Hayati, Asfitri; Kartini, Raden Asri (Universitas Muhammadiyah Tangerang, 2023)
Students are certainly familiar with the term scientific work. Scientific work is written work that contains an explanation of a scientific discussion carried out by a writer or researcher. Scientific work is written work, specifically writing a thesis. For every student completing their studies, they are required to write a scientific work, because it is a regulation in higher education that they will graduate or get a degree when they have completed all the demands in higher education, namely writing a thesis. So it is necessary to hold training in writing Scientific Writing (KTI) for tourism study program students, Faculty of Tourism and Creative Industries, Universitas Muhammadiyah Tangerang. With this training activity, it is hoped that students will be able to increase their knowledge and skills in writing scientific papers, namely writing theses or other scientific works. The methods used in this service or training in writing scientific papers are the lecture method, discussion method and writing practice method. This training was carried out over three meetings starting from Tuesday to Thursday 17-19 October 2023. The training participants were 20 tourism study program students from the Faculty of Tourism and Creative Industries. Based on the results of the training. Students are trained in choosing titles and determining topics and creating an outline for an essay. Students are able to write problem formulations well by following the systematics of writing scientific papers. With the level of student ability in the training process, the level of student ability in understanding how to choose a title is 80%, compiling an outline online is 82%, practicing writing is 75%, while students find it difficult to determine a topic at 5%.Students are certainly familiar with the term scientific work. Scientific work is written work that contains an explanation of a scientific discussion carried out by a writer or researcher. Scientific work is written work, specifically writing a thesis. For every student completing their studies, they are required to write a scientific work, because it is a regulation in higher education that they will graduate or get a degree when they have completed all the demands in higher education, namely writing a thesis. So it is necessary to hold training in writing Scientific Writing (KTI) for tourism study program students, Faculty of Tourism and Creative Industries, Universitas Muhammadiyah Tangerang. With this training activity, it is hoped that students will be able to increase their knowledge and skills in writing scientific papers, namely writing theses or other scientific works. The methods used in this service or training in writing scientific papers are the lecture method, discussion method and writing practice method. This training was carried out over three meetings starting from Tuesday to Thursday 17-19 October 2023. The training participants were 20 tourism study program students from the Faculty of Tourism and Creative Industries. Based on the results of the training. Students are trained in choosing titles and determining topics and creating an outline for an essay. Students are able to write problem formulations well by following the systematics of writing scientific papers. With the level of student ability in the training process, the level of student ability in understanding how to choose a title is 80%, compiling an outline online is 82%, practicing writing is 75%, while students find it difficult to determine a topic at 5%.